Bandgap Tuning and Blue-Green Band Emissions of Sol-Gel Synthesized ZnO Films by High Cu Doping - Fatehmulla, Amanullah; AlDawood, Iqram Abdulkarim; Qindeel, Rabia; Aldhafiri, A. M.; Albassam, A. A.; Shahabuddin, M.; Yakuphanoğlu, Fahrettin (Amer Scientific Publishers, 2020)
The present research focuses on the preparation of ZnO thin films both undoped and doped with varying Cu concentrations (0.0%, 0.8%, 3.0%, 5.0%, 10.0% and 20.0%) using sol-gel spin coating technique. The optical bandgap (E-g) for undoped films is recorded as 3.239 eV and shows a little increase to 3.248 eV when it is doped with 0.8% Cu concentration whereas further increase of Cu doping concentration, it is decreased from 3.248 eV to 3.107 eV for 20% Cu. The E-U (Urbach Energy) is improved with the enhancement of Cu doping concentration. Ultraviolet (UV) and bluegreen band emissions are noticed from PL (photoluminescence) spectra. The UV peak intensities are diminished with increasing Cu doping concentration while the blue peaks intensities are amplified. These results illustrate that ZnO films doped with Cu meet the requirement for applications in different blue emission devices.
Keywords: ZnO:Cu; Sol-Gel Synthesis; Nanoarchitectonics; Bandgap Tuning; Urbach Energy; Blue-Green Band Emissions